Relationship between lactate-to-albumin ratio and all-cause mortality among critically ill pediatric patients: Results from the pediatric intensive care database - Xiangyu Zuo; Yongfu Song; Jun Liu (PLoS ONE, 2026)
Background The lactate-to-albumin ratio (LAR) has emerged as a valuable prognostic marker in adult critically ill patients. However, evidence regarding its association with mortality in pediatric intensive care unit (ICU) patients remains limited. The present study utilized data from the Pediatric Intensive Care (PIC) database to investigate the relationship between LAR and clinical outcomes among critically ill pediatric patients. Methods This study enrolled 4,162 pediatric patients from the PIC database as study participants. A piecewise multivariate Cox regression model was constructed, incorporating subgroup analysis and restricted cubic spline (RCS) curve analysis, to investigate the association between the LAR and all-cause mortality during hospitalization and ICU stay. Results In the fully adjusted model, for every one-unit increase in LAR, the risk of in-hospital mortality increased by 23% (HR: 1.23, 95% CI: 1.17–1.30), and the risk of ICU mortality increased by 22% (HR: 1.22, 95% CI: 1.15–1.28). The risk of in-hospital mortality and ICU mortality for patients in the highest LAR quartile were 2.30 and 2.17 times those of patients in the lowest quartile, respectively. RCS analysis revealed a non-linear positive correlation between LAR and 30-day all-cause mortality in critically ill children, with a threshold of 0.4468. Moreover, the predictive performance of LAR (AUC = 0.725) was superior to that of lactate alone (AUC = 0.712) or albumin alone (AUC = 0.608). Conclusions Research shows that in critically ill pediatric patients, LAR is nonlinearly and positively correlated with the 30-day all-cause mortality rate. Moreover, the higher the LAR value, the more significantly the mortality rate increases, suggesting that it is a promising predictor for short-term mortality risk, although this requires further prospective validation.